Option C:
The coefficient of
is 40.
Solution:
Given expression:
![(2 x+y)^{5}](https://tex.z-dn.net/?f=%282%20x%2By%29%5E%7B5%7D)
Using binomial theorem:
![(a+b)^{n}=\sum_{i=0}^{n}\left(\begin{array}{l}n \\i\end{array}\right) a^{(n-i)} b^{i}](https://tex.z-dn.net/?f=%28a%2Bb%29%5E%7Bn%7D%3D%5Csum_%7Bi%3D0%7D%5E%7Bn%7D%5Cleft%28%5Cbegin%7Barray%7D%7Bl%7Dn%20%5C%5Ci%5Cend%7Barray%7D%5Cright%29%20a%5E%7B%28n-i%29%7D%20b%5E%7Bi%7D)
Here ![a=2 x, b=y](https://tex.z-dn.net/?f=a%3D2%20x%2C%20b%3Dy)
Substitute in the binomial formula, we get
![(2x+y)^5=\sum_{i=0}^{5}\left(\begin{array}{l}5 \\i\end{array}\right)(2 x)^{(5-i)} y^{i}](https://tex.z-dn.net/?f=%282x%2By%29%5E5%3D%5Csum_%7Bi%3D0%7D%5E%7B5%7D%5Cleft%28%5Cbegin%7Barray%7D%7Bl%7D5%20%5C%5Ci%5Cend%7Barray%7D%5Cright%29%282%20x%29%5E%7B%285-i%29%7D%20y%5E%7Bi%7D)
Now to expand the summation, substitute i = 0, 1, 2, 3, 4 and 5.
![$=\frac{5 !}{0 !(5-0) !}(2 x)^{5} y^{0}+\frac{5 !}{1 !(5-1) !}(2 x)^{4} y^{1}+\frac{5 !}{2 !(5-2) !}(2 x)^{3} y^{2}+\frac{5 !}{3 !(5-3) !}(2 x)^{2} y^{3}](https://tex.z-dn.net/?f=%24%3D%5Cfrac%7B5%20%21%7D%7B0%20%21%285-0%29%20%21%7D%282%20x%29%5E%7B5%7D%20y%5E%7B0%7D%2B%5Cfrac%7B5%20%21%7D%7B1%20%21%285-1%29%20%21%7D%282%20x%29%5E%7B4%7D%20y%5E%7B1%7D%2B%5Cfrac%7B5%20%21%7D%7B2%20%21%285-2%29%20%21%7D%282%20x%29%5E%7B3%7D%20y%5E%7B2%7D%2B%5Cfrac%7B5%20%21%7D%7B3%20%21%285-3%29%20%21%7D%282%20x%29%5E%7B2%7D%20y%5E%7B3%7D)
![$+\frac{5 !}{4 !(5-4) !}(2 x)^{1} y^{4}+\frac{5 !}{5 !(5-5) !}(2 x)^{0} y^{5}](https://tex.z-dn.net/?f=%24%2B%5Cfrac%7B5%20%21%7D%7B4%20%21%285-4%29%20%21%7D%282%20x%29%5E%7B1%7D%20y%5E%7B4%7D%2B%5Cfrac%7B5%20%21%7D%7B5%20%21%285-5%29%20%21%7D%282%20x%29%5E%7B0%7D%20y%5E%7B5%7D)
Let us solve the term one by one.
![$\frac{5 !}{0 !(5-0) !}(2 x)^{5} y^{0}=32 x^{5}](https://tex.z-dn.net/?f=%24%5Cfrac%7B5%20%21%7D%7B0%20%21%285-0%29%20%21%7D%282%20x%29%5E%7B5%7D%20y%5E%7B0%7D%3D32%20x%5E%7B5%7D)
![$\frac{5 !}{1 !(5-1) !}(2 x)^{4} y^{1} = 80 x^{4} y](https://tex.z-dn.net/?f=%24%5Cfrac%7B5%20%21%7D%7B1%20%21%285-1%29%20%21%7D%282%20x%29%5E%7B4%7D%20y%5E%7B1%7D%20%3D%2080%20x%5E%7B4%7D%20y)
![$\frac{5 !}{2 !(5-2) !}(2 x)^{3} y^{2}= 80 x^{3} y^{2}](https://tex.z-dn.net/?f=%24%5Cfrac%7B5%20%21%7D%7B2%20%21%285-2%29%20%21%7D%282%20x%29%5E%7B3%7D%20y%5E%7B2%7D%3D%2080%20x%5E%7B3%7D%20y%5E%7B2%7D)
![$\frac{5 !}{3 !(5-3) !}(2 x)^{2} y^{3}= 40 x^{2} y^{3}](https://tex.z-dn.net/?f=%24%5Cfrac%7B5%20%21%7D%7B3%20%21%285-3%29%20%21%7D%282%20x%29%5E%7B2%7D%20y%5E%7B3%7D%3D%2040%20x%5E%7B2%7D%20y%5E%7B3%7D)
![$\frac{5 !}{4 !(5-4) !}(2 x)^{1} y^{4}= 10 x y^{4}](https://tex.z-dn.net/?f=%24%5Cfrac%7B5%20%21%7D%7B4%20%21%285-4%29%20%21%7D%282%20x%29%5E%7B1%7D%20y%5E%7B4%7D%3D%2010%20x%20y%5E%7B4%7D)
![$\frac{5 !}{5 !(5-5) !}(2 x)^{0} y^{5}=y^{5}](https://tex.z-dn.net/?f=%24%5Cfrac%7B5%20%21%7D%7B5%20%21%285-5%29%20%21%7D%282%20x%29%5E%7B0%7D%20y%5E%7B5%7D%3Dy%5E%7B5%7D)
Substitute these into the above expansion.
![(2x+y)^5=32 x^{5}+80 x^{4} y+80 x^{3} y^{2}+40 x^{2} y^{3}+10 x y^{4}+y^{5}](https://tex.z-dn.net/?f=%282x%2By%29%5E5%3D32%20x%5E%7B5%7D%2B80%20x%5E%7B4%7D%20y%2B80%20x%5E%7B3%7D%20y%5E%7B2%7D%2B40%20x%5E%7B2%7D%20y%5E%7B3%7D%2B10%20x%20y%5E%7B4%7D%2By%5E%7B5%7D)
The coefficient of
is 40.
Option C is the correct answer.